Development of Autonomous Sweeper Robot for Badminton Court - Taher, Mohd Fahmi; Harun, Mohamad Haniff; Mohd Annuar, Khalil Azha; Mohd Ab Halim, Mohd Firdaus; Mohd Aras, Mohd Shahrieel; Azahar, Arman Hadi; Zainal Abidin, Amar Faiz (2016)
Badminton court cleaner robot is one of the robots of the innovation project and yet being develops by other society. The most dominant reason of this creation, this project can ease badminton court practitioner organizer to clean up the court after match, instead of using the manual way which is individual clean up the court. In additional from the observation, interview section the organization agrees and felt satisfied with this project and welcome an innovative robot. This project created this robot with the fundamental of square shape for the body and combined the entire element such as microcontroller, actuator, vacuum, sweeper, and DC motor. This automatic vacuum robot of badminton court can just be switch on by click one button and the robot will make a move to start their cleaning job in a short time. In a nut shell, this robot can reduce labor cost and time concern and as well as the challenge of vision 2020.